Work Behavior of Female Workers in the Informal Sector in Kupang, East Nusa Tenggara - Noorce Christiani Berek; Luh Putu Ruliati; Helga Jillvera Nathalia Ndun; Diana Juniati Nabuasa (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: Work behavior refers to an individual's actions while working, whether or not following procedure. Work behavior following the procedure will prevent accidents. Workers in the informal sector pay less attention to proper work behavior, which may lead to accidents in the workplace. The theory planned behavior (TPB) maintains that three core components, namely attitude, subjective norm, and perceived behavioral control, together shape an individual’s behavioral intention. In turn, behavioral intention determines human behavior. This study aimed to analyze factors that influence work behavior in female workers in the informal sector, using TPB.Subjects and Method: This was a cross-sectional study conducted in Kupang, East Nusa Tenggara, from April to July 2019. A sample of 548 female workers in the informal sector was selected at random. The dependent variable was work behavior. The independent variables were subjective norm, perceived behavior control, and attitude toward behavior. The data were collected through interview using questionnaire. Bivariate analysis was performed by simple linear regression.Results: Proper work behavior increased with strong intention (b= 1.03; 95% CI= 5.20 to 7.26; p< 0.001), positive attitude (b= 0.54; 95% CI= 6.30 to 7.40; p< 0.001), favorable subjective norm (b= 1.11; 95% CI= 5.68 to 7.90; p< 0.001), and strong perceived behavior control (b= 1.17; 95% CI= 5.75 to 8.09; p< 0.001).Conclusion: Proper work behavior increases with strong intention, positive attitude, favorable subjective norm, and strong perceived behavior control.Keywords: attitude, subjective norm, perceived behavioral control, intention, work behavior, female workers.Correspondence:Noorce Christiani Berek. Faculty of Public Health, Universitas Nusa Cendana, Kupang. Jl. Adi Sucipto Penfui, Kupang, East Nusa Tenggara. Email: noorce.berek@staf.undana.ac.id. Mobile: 081228521127. Journal of Health Promotion and Behavior (2022), 07(02): 161-169DOI: https://doi.org/10.26911/thejhpb.2021.07.02.08